Hazara nairovirus elicits differential induction of apoptosis and nucleocapsid protein cleavage in mammalian and tick cells. (5th February 2019) - Fuller, J.; Surtees, R. A.; Shaw, A. B.; Álvarez-Rodríguez, B.; Slack, G. S.; Bell-Sakyi, Lesley; Mankouri, J.; Edwards, T. A.; Hewson, R.; Barr, J. N.
Abstract : The Nairoviridae family within the Bunyavirales order comprise tick-borne segmented negative-sense RNA viruses that cause serious disease in a broad range of mammals, yet cause a latent and lifelong infection in tick hosts. An important member of this family is Crimean-Congo haemorrhagic fever virus (CCHFV), which is responsible for serious human disease that results in case fatality rates of up to 30 %, and which exhibits the most geographically broad distribution of any tick-borne virus. Here, we explored differences in the cellular response of both mammalian and tick cells to nairovirus infection using Hazara virus (HAZV), which is a close relative of CCHFV within the CCHFV serogroup. We show that HAZV infection of human-derived SW13 cells led to induction of apoptosis, evidenced by activation of cellular caspases 3, 7 and 9. This was followed by cleavage of the classical apoptosis marker poly ADP-ribose polymerase, as well as cellular genome fragmentation. In addition, we show that the HAZV nucleocapsid (N) protein was abundantly cleaved by caspase 3 in these mammalian cells at a conserved DQVD motif exposed at the tip of its arm domain, and that cleaved HAZV-N was subsequently packaged into nascent virions. However, in stark contrast, we show for the first time that nairovirus infection of cells of the tick vector failed to induce apoptosis, as evidenced by undetectable levels of cleaved caspases and lack of cleaved HAZV-N. Our findings reveal that nairoviruses elicit diametrically opposed cellular responses in mammalian and tick cells, which may influence the infection outcome in the respective hosts.